Remission for Correctional Inmates: Legal Requirements and Societal Impacts in Cases of Corruption, Terrorism, and Narcotics - Arief Budi Wicaksono; Hartoyo Hartoyo; Fathul Hamdani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Remission constitutes a right granted to inmates who meet specific requirements as a form of recognition for good behavior during imprisonment. This study aims to examine the requirements for granting remission to correctional inmates and analyze the societal impacts when remission is given to convicts of corruption, terrorism, and narcotics offenses. The research employs a normative juridical approach through a literature study. The findings demonstrate that remission possesses a clear legal foundation encompassing both general and specific requirements, particularly for perpetrators of serious crimes. General requirements include serving at least six months of imprisonment, demonstrating good behavior, and actively participating in guidance programs. For special crime perpetrators, additional requirements apply, including becoming justice collaborators, paying fines and compensation, and participating in deradicalization programs. However, granting remission to special crime convicts generates negative impacts on public perception of justice, deterrence effects, and the integrity of law enforcement. The research concludes that a more selective and accountable remission policy supported by public oversight is necessary to align with the objectives of correctional guidance and legal justice.